The Secret Life of Lobsters: How Fishermen and Scientists Are Unraveling the Mysteries of Our Favorite Crustacean (Book). - Christensen, Bryce (Booklist, 2004)
Reviews the book “The Secret Life of Lobsters: How Fishermen and Scientists Are Unraveling the Mysteries of Our Favorite Crustacean,” by Trevor Corson.